2015
DOI: 10.1111/ced.12724
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency caused by a nonsense mutation inNCSTNunderlying hidradenitis suppurativa in a Chinese family

Abstract: Hidradenitis suppurativa (HS) is a chronic disease of follicular occlusion. It involves the axilla, groin, perianal and perineal regions, and is characterized by recurrent draining sinuses, skin abscesses and disfiguring scars. Loss-of-function mutations in the genes encoding γ-secretase have been identified as a cause of HS. We collected skin samples from three patients with HS from a Chinese family carrying a NCSTN mutation (c.1258C>T (p.Q420X)) and three unrelated healthy controls (HCs). Expression level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…PASH syndrome was first described in 2012, distinguishing it from PAPA syndrome, in the absence of pyogenic arthritis and the lack of a pathogenic mutation in the PSTPIP1 gene. Nevertheless, lack of onset of arthritis in a female patient with PAPA has also been reported . PSTPIP1 encodes proline–serine–threonine phosphatase‐interacting protein 1, which is known to be a cytoskeleton‐associated adaptor protein of the inflammasome, a fundamental protein complex, which has been implicated in the inflammatory signalling pathway .…”
Section: Summary Of Clinical Presentations In the Current Case And Inmentioning
confidence: 98%
See 1 more Smart Citation
“…PASH syndrome was first described in 2012, distinguishing it from PAPA syndrome, in the absence of pyogenic arthritis and the lack of a pathogenic mutation in the PSTPIP1 gene. Nevertheless, lack of onset of arthritis in a female patient with PAPA has also been reported . PSTPIP1 encodes proline–serine–threonine phosphatase‐interacting protein 1, which is known to be a cytoskeleton‐associated adaptor protein of the inflammasome, a fundamental protein complex, which has been implicated in the inflammatory signalling pathway .…”
Section: Summary Of Clinical Presentations In the Current Case And Inmentioning
confidence: 98%
“…The molecular basis of PASH syndrome is not fully understood, and the absence of pathogenic mutations in the PSTPIP1 gene has been used in some way to differentiate it from other AIDs, such as PAPA (pyogenic arthritis, pyoderma gangrenosum and acne) and PAPASH (pyogenic arthritis and PASH), with which PASH syndrome exhibits some clinical overlap . PASH syndrome has been recently associated with a pathogenic mutation in the NCSTN gene, which has also been found in a family with hidradenitis suppurativa . Other gene mutations in NOD (nucleotide‐binding oligomerization domain) genes, MEFV and the immunoproteasome have also been observed in some cases of PASH syndrome …”
Section: Summary Of Clinical Presentations In the Current Case And Inmentioning
confidence: 99%
“…HS patients have mutations in genes ( NCSTN , PSENEN , PSEN1 ) that code for subunits of γ-secretase, which normally cleaves Notch receptor, a transmembrane protein involved in epidermal and follicular development and differentiation [23, 24]. Notably, a significant number of these studies were conducted in Chinese populations [25-27]. Although 1 study identified a mutation in NCSTN in an African family [28], genetic studies of HS in SOC are lacking, despite a higher prevalence of HS in these populations.…”
Section: Geneticsmentioning
confidence: 99%
“…The overall nature of the mutations reported in HS and the available functional data would suggest that they are loss‐of‐function variants. Some of the mutations have been shown to result in haploinsufficiency of their respective components . Given that mutations have been reported in three of the four γ‐secretase enzyme complex components it has been hypothesized that these mutations may affect enzyme activity, but this has not been proven in studies performed to date .…”
Section: Pathogenesismentioning
confidence: 99%
“…Some of the mutations have been shown to result in haploinsufficiency of their respective components. 85,86 Given that mutations have been reported in three of the four c-secretase enzyme complex components it has been hypothesized that these mutations may affect enzyme activity, but this has not been proven in studies performed to date. 86 The recent genetic findings are supported by in vivo data showing that knockdown of individual c-secretase components in mouse skin (PSEN1 À PSEN2 À , PSEN1 À and NCSTN AE ) results in follicular keratinization, follicular atrophy and the formation of epidermal cysts.…”
Section: Geneticsmentioning
confidence: 99%